Analisis Peran Pendidikan Dalam Membentuk Kesadaran Akan Hak dan Kewajiban Warganegara di Kalangan Generasi Muda Indonesia - Ulviana Agustina; Ersa Wiriani Safitri; Melda Anjelia (International Forum of Researchers and Lecturers, 2025)
Considering that the millennial generation will continue the life of the nation and state, the millennial generation needs to be made aware of the importance of preserving the country. This will support the country's defense against internal and external, military and non-military threats. Because education helps future generations of young people understand history, values, and dedication to preserving the country, education is very important for national defense. Students can become development agents who benefit society and the nation through education and learning how important it is to maintain national unity. This research will use normative juridical research which takes an approach from legal, phenomenon and ideological perspectives. This article aims to determine the extent to which formal education in Indonesia influences the development of awareness of national defense in the younger generation, explores the factors that influence this understanding and awareness, examines how the national education curriculum is implemented, and provides suggestions for strengthening the education system. The advantages of this work are as follows: it provides an in-depth analysis of how education forms a strong concept of national defense knowledge for the younger generation